Access to infertility investigations and treatment for HIV+ people: a survey of Australian infertility clinics - Marian Pitts; Penelope Shields (Elsevier, 2004)
Abstract Objective:To examine the availability in Australia of investigations and treatment of infertility for people infected with HIV. Methods:The study was a questionnaire survey of all identified Australian IVF clinics undertaken in 2002. All clinics potentially offering investigations and treatments for IVF were contacted (52) and invited to return a survey concerning people infected with HIV. Results:Thirty‐one (59.6%) clinics responded. Fourteen (45.2%) clinics had seen 24 HIV+ patients in the past 12 months. Twenty (64.5%) clinics had a policy on HIV. In nearly all clinics (n=29), an HIV+ man or woman would be offered investigations; 28 clinics indicated they would offer investigations when both partners were positive. Treatments would be offered by 26 clinics if the man was HIV+, by 23 clinics if the woman was HIV+, and by 24 clinics if both were HIV+. Conclusions:Infertility treatment in Australia for HIV+ people is available. Couples will more than likely receive both investigations and treatment. There are marked differences between States and Territories in the numbers of HIV+ people reported seen at the clinics. Implications:There is currently variable access and policies with regard to infertility treatment for HIV+ people in Australia. It is likely that demand for these services will increase.